2018
DOI: 10.1111/acps.12998
|View full text |Cite
|
Sign up to set email alerts
|

Depression precedes, but does not follow, gestational diabetes

Abstract: Objectives To determine whether past history of depression is associated with increased rates of gestational diabetes, and whether history of gestational diabetes is associated with increased rates of postpartum depression. Research design Data for this case–control study consisted of de‐identified chart records for 1439 women who received pregnancy care at a large university hospital between 1998 and 2017. Results A history of depression prior to pregnancy was associated with gestational diabetes requiring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…An initial search identified 20,040 studies, of which, those with limited discussions in relation to MH outcomes and of poor quality, were excluded, resulting in a final dataset of 69 studies ( Table 1a ) of which 46 studies were systematically included and thematically analysed ( Table 2 ). These 46 studies included 26 qualitative [ 12 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], 17 cohort [ 7 , 18 , 21 , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], 6 controlled [61] , [62] , [63] , [64] , [65] , [66] , 2 randomised controlled trials [ 19 , 67 ] and 2 mixed methods [ 68 , 69 ] studies. Based on the eligibility criteria, and the quality assessment, 21 studies were selected for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial search identified 20,040 studies, of which, those with limited discussions in relation to MH outcomes and of poor quality, were excluded, resulting in a final dataset of 69 studies ( Table 1a ) of which 46 studies were systematically included and thematically analysed ( Table 2 ). These 46 studies included 26 qualitative [ 12 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], 17 cohort [ 7 , 18 , 21 , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], 6 controlled [61] , [62] , [63] , [64] , [65] , [66] , 2 randomised controlled trials [ 19 , 67 ] and 2 mixed methods [ 68 , 69 ] studies. Based on the eligibility criteria, and the quality assessment, 21 studies were selected for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Nicklas and colleagues reported that ethnicity did not alter the risk of PPD [9] , following adjustments for demographic variables. 2 studies reported that GDM did not alter the risk of PND in Hispanic [55] and Iranian [65] women. Another large cohort study reported that African American women with GDM had a lower risk of PPD in comparison with Caucasians [21] .…”
Section: Discussionmentioning
confidence: 98%
“…Research to date on the relationship between GDM and CMD during pregnancy has yielded mixed results; some studies have found evidence of an association, while others have not ( Byrn and Penckofer, 2013 ; Ross et al., 2016 ). The smaller number of studies examining the association between CMD prior to pregnancy and subsequent GDM have provided evidence supporting a relationship ( Beka et al., 2018 ; Bowers et al., 2013 ; Clark et al., 2019 ). Our own meta-analysis of studies during pregnancy and up to one year postpartum, while finding an increased risk of depression in women with GDM during pregnancy, found substantial heterogeneity between studies measuring both symptoms and diagnoses of depression and anxiety ( Wilson et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies were of a UK population and despite an increasing awareness of the influence of preconception mental health on pregnancy outcomes ( Patton et al., 2018 ; Wilson et al., 2018 ) there have been few studies investigating the risk of GDM in women with preconception mental disorders. A small number of North American cohorts have found an increased risk of GDM in women with anxiety and depression prior to pregnancy ( Beka et al., 2018 ; Bowers et al., 2013 ; Clark et al., 2019 ) but it is not clear the extent to which these findings generalise to a UK population.…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown by a multitude of studies and meta analyses which demonstrated that GDM increases the risk to develop not only type 2 diabetes [8,9] but also the metabolic syndrome [10,11], cardiovascular disease [12] and some form of cancer [13]. A potential association with depression is currently controversially discussed [14,15].…”
Section: Introductionmentioning
confidence: 99%